Analisis Minimalisasi Biaya Obat Antihipertensi antara Kombinasi Ramipril-Spironolakton dengan Valsartan pada Pasien Gagal Jantung Kongestif di Rumah Sakit Pemerintah XY di Jakarta Tahun 2014 - Rahmawati, Cyntiya; Nurwahyuni, Atik (UI Scholars Hub, 2017)
Hypertension is one of risk factors for congestive heart failure as the top 10 most prevalent diseases in XY Public Hospital in 2014. It has a large number of total cost and cost deviation between hospital and JKN rate. This study aimed to choose an alternative that is more cost-effective to treat congestive heart failure at XY Hospital in 2014. This was a quantitative research using retrospective cross-sectional analysis. The study compared the average value of total cost of two alternative treatments, ramipril-spironolactone with valsartan by using Hospital’s perspective. Direct medical cost components were cost of drugs, cost of physicians’ services and cost of hospitalizations. This study found that: (1) The average total cost of ramipril-spironolactone was Rp.2.527.743; whereas the average total cost of valsartan was Rp.2.430.923; (2) Ramipril-spironolactone’s effectiveness was not significantly different from valsartan; (3) There was cost saving on the average of total cost using valsartan’s drug as many as Rp96.820 per patient; (4) There was cost saving on hospitalization cost using valsartan’s drug for Rp299.031 per patient. Valsartan provided the lowest value and more cost-effective than ramipril-spironolactone for patient with congestive heart failure.